2021
DOI: 10.1037/fam0000841
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment and parent–offspring interaction: A multigenerational extended family design.

Abstract: In the current study, the associations between multiple types of child maltreatment (CM), parent-offspring interactions, and family cohesion were examined in an extended family study. A total of 366 parentoffspring pairs from 137 nuclear families participated. Parents (M age = 52.8 years, age range: 26.6-88.4 years, 57% female) reported about perpetrated CM and offspring (M age = 25.7 years, range: 7.5-65.5 years, 58% female) about experienced CM during their childhood. Parent-offspring interactions were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Previous findings showed that resemblance of parent‐to‐offspring communications among offspring siblings was moderate (Buisman et al, 2021). Here, when looking separately at mothers' and fathers' warmth and negativity, we found that mothers were highly concordant toward multiple offspring in their warmth and negativity (ICC MtO warmth = .55; ICC MtO negativity = .47).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Previous findings showed that resemblance of parent‐to‐offspring communications among offspring siblings was moderate (Buisman et al, 2021). Here, when looking separately at mothers' and fathers' warmth and negativity, we found that mothers were highly concordant toward multiple offspring in their warmth and negativity (ICC MtO warmth = .55; ICC MtO negativity = .47).…”
Section: Resultsmentioning
confidence: 93%
“…Yet, the majority of studies on the associations of psychological problems and parent–offspring communication focuses on mothers with their child and/or adolescent offspring (Gar & Hudson, 2008; Milan & Carlone, 2018), whereas research on associations between psychological problems and fathers' interactions with their offspring is relatively scarce. Results from our sample showed that within a family, the correlation between fathers' and mothers' communication style was .10, suggesting that mothers and fathers communicate differently with the same child (Buisman et al, 2021). Thus, investigating offspring interacting with both parents is of importance to elucidate the associations of psychological problems with parent–offspring communication in fathers and mothers.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations